Exploring the International Students’ Perceptions of the Indonesian Teaching Materials to Enhance Their Willingness to Communicate - Aguskin, Lewinna Christiani; Maryani, Maryani (Bina Nusantara University, 2018)
This research had been conducted to investigate Indonesian teaching materials which corresponded with the Willingness to Communicate (WTC) in Indonesian to facilitate students’ learning. Therefore, this case study was conducted in Indonesian Language for Foreigners (BIPA) classes at a private university in Bandung, Indonesia. The objectives of the research were; to investigate BIPA students’ perceptions of the current language learning materials used; to discover to what extent the international students’ WTC was influenced by the current language material; and to explore the BIPA teachers’ strategies in developing language materials that facilitate the students’ WTC inside and outside the classroom. Semi-structured-interviews with seven BIPA students and four teachers and classroom recordings were used to collect data. Thematic analysis and descriptive statistics were used in data analysis. The findings show that the listening activities and interview assignments implemented in the current language materials, also the teachers’ strategies in class, such as using authentic materials and social media have positively impacted the students’ WTC. The findings of this research contribute to the classroom practice and material development of Indonesian to facilitate students’ learning and increase students’ WTC in Indonesian.